Phytoplankton Production for Research and Teaching in Larviculture Shrimp, Shellfish and Fish, 2008-2013 - Arias-Valverde, Sidey (2016)
From 2008 to 2013 production of marine phytoplankton was a miscellaneous activity that supporter teaching, investigation and extension. For this, improvements were made annually in the massive production, maintenance of stock and intermediates; considering the factors of tension detected last year, five fundamental products are reported: 1- acquisition of 11 certified species, 2- improvements in massive production protocols, 3- isolation of two endogenous species to the Gulf of Nicoya, 4- acclimation and scaling to 2 Tons of one species endogenous to the Gulf of Nicoya classifies as spl. And 5- a 60% increment in the production of massive cultures. During this period, 10 species were used as didactic material in 7 courses of levels III and IV of the Marine Biology career. The results accomplished indicate that this activity has contributed to the development of teaching, investigation and extension that promotes the School of Biological Sciences. It is important to continue the task of acquiring endemic, acclimated species that are identified and validated as a source of live food, through the biochemical characterization of the nutritional profile in the isolated species.